Experimental behavior of precast HSFRC columns in steel socket foundation under cyclic loads. (1st November 2015) - Germano, Federica; Tiberti, Giuseppe; Plizzari, Giovanni; Colombo, Antonella
Highlights: Presentation of eleven tests on full-scale precast RC/SFRC columns under cyclic load. SFRC reduces the spalling of concrete cover and the buckling of longitudinal rebars. SFRC enhances structural behavior of columns up to drift levels of about 5%. SFRC having a higher toughness enables a better crack control. Abstract: The present paper aims to investigate the influence of steel fibers on the behavior of high strength precast concrete columns in steel socket foundation under cyclic loading. The experimental program was mainly defined to study the effects of the volume fraction and the type of fibers on the behavior of full-scale precast columns subjected to reversed cyclic horizontal loading under constant axial load. Experimental parameters under investigation were: the transverse reinforcement ratio, the axial load, the fiber type and content as well as the effect of steel-to-concrete bond of rebars in the critical region. The latter was investigated since it could considerably govern the local ductility in terms of curvature and of global displacement of the precast column, especially in presence of fibrous reinforcement. Experimental results highlight the importance of the stirrup spacing in the critical region as well as the positive effect of fibers on the crack development, by preventing the concrete cover to spall-out at earlier stages. Steel Fiber Reinforced Concrete (SFRC) tends to enhance the structural stiffness, the strength and the dissipated energy.